Land consolidation drives changes in soil bacterial community structure and promotes positive bacterial interactions - Haokun Shi; Yaoben Lin; Siyi Huang; Lei Wang (PLoS ONE, 2025)
Understanding how land consolidation influences bacterial community structure and interactions is essential for advancing ecological restoration and sustainable land management. However, current knowledge remains insufficient regarding the micro-scale ecological effects of this comprehensive management practice. This study investigated an arable land consolidation project in the Yangtze River Delta plain, where 50 soil samples were collected from consolidated (n = 36) and non-consolidated (n = 14) paddy fields. A comparative analysis was conducted to evaluate the impacts of land consolidation on soil microbial community structure and ecological processes. The findings revealed that land consolidation significantly altered edaphic factors, with moisture content, pH, total nitrogen, and organic matter identified as the dominant drivers of bacterial community structure. Consolidation also reduced the influence of spatial heterogeneity on community composition. Variance partitioning analysis showed edaphic variables (8.84%) and land consolidation (4.34%) significantly contributed to the variations in bacterial community structure. Consolidated fields exhibited a better fit to the neutral community model, suggesting that land consolidation may improve the migration ability of bacterial communities by enhancing soil homogeneity and reducing habitat isolation. The broader niche breadth observed in land consolidation fields further indicated that bacterial communities possess stronger environmental adaptability and community stability, providing a foundation for positive interactions. Interaction analyses revealed higher species coexistence after land consolidation, characterized by stronger positive cohesion and a higher proportion of positive associations in co-occurrence networks. Collectively, these findings suggest that land consolidation could promote positive bacterial interactions, potentially enhancing overall community stability.